142 Urban–rural traumatic brain injury mortality disparities by age and mechanism of injury. (5th May 2020) - Womack, Lindsay; Daugherty, Jill; Sarmiento, Kelly; Waltzman, Dana
Abstract : Statement of Purpose: Traumatic brain injury (TBI) mortality rates have been shown to be higher in rural versus urban areas. Variation by age and intent/mechanism of injury has not been assessed. Urban–rural TBI mortality rate differences were quantified by age and intent/mechanism of injury. Methods/Approach: National Vital Statistics System mortality data (2015–2017) were analyzed by three urban–rural county classifications: large urban, medium/small urban, and rural. Excess TBI mortality rates were calculated relative to large urban areas (rate differences), which had the lowest TBI mortality rates. The proportions of deaths attributable to differences in urbanization (population attributable fraction) were estimated by dividing excess deaths by total TBI deaths. The proportions of the excess deaths due to each intent/mechanism were calculated by dividing the intent/mechanism-specific excess deaths from the total excess deaths by urbanization level and age group. Results: Rural areas had the highest excess TBI mortality rates. Overall, 18.1% of TBI deaths would be prevented if all areas had the TBI mortality rate of large urban areas. Excess TBI mortality rates in rural and medium/small urban areas were primarily due to motor vehicle crashes (33.2% and 28.5%) and intentional self-harm (38.9% and 44.8%). This was consistent for all age groups except individuals aged ≥75 years in medium/small urban areas, for whom unintentional falls and intentional self-harm accounted for the largest share of excess TBI mortality rates. Conclusions: TBI mortality increased with rurality and excess TBI mortality rates were predominantly attributable to motor vehicle crashes and intentional self-harm, with differences by age regarding magnitude and mechanism. Significance and Contributions to Injury and Violence Prevention Science: TBI mortality increases with rurality. Prevention in rural areas may want to focus efforts on reducing TBI-related deaths due to motor vehicle crashes, intentional self-harm, and falls among older adults.